1995
DOI: 10.1007/bf01856537
|View full text |Cite
|
Sign up to set email alerts
|

Finite population corrections for ranked set sampling

Abstract: Linear range, observational economy, order statistics from finite populations, quadratic range, relative savings, sampling efficiency, sampling from finite populations, sampling without replacement,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
35
0

Year Published

2002
2002
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(35 citation statements)
references
References 3 publications
0
35
0
Order By: Relevance
“…They showed that the RSS estimator of the population mean is unbiased and they derived an explicit formula for its variance when the set size is k = 2 and the underlying population has a discrete uniform distribution. Patil et al (1995) extended this result to more general finite populations and to larger set sizes. Takahasi and Futatsuya (1998) showed that, when samples are drawn without replacement, the relative precision of the RSS estimator of the population mean relative to the SRS estimator with the same number of units quantified, is bounded above by 1.…”
mentioning
confidence: 79%
“…They showed that the RSS estimator of the population mean is unbiased and they derived an explicit formula for its variance when the set size is k = 2 and the underlying population has a discrete uniform distribution. Patil et al (1995) extended this result to more general finite populations and to larger set sizes. Takahasi and Futatsuya (1998) showed that, when samples are drawn without replacement, the relative precision of the RSS estimator of the population mean relative to the SRS estimator with the same number of units quantified, is bounded above by 1.…”
mentioning
confidence: 79%
“…However, we are awaiting appropriate data collected using ranked set sampling, and future work will apply the RSBLUQE to real-data assessments for newly proposed statistically verifiable ideal standards. We also propose to consider using the RSBLUQE in finite population applications, perhaps for the picking of observations from a finite group of air quality monitoring stations, and we hope to develop the necessary theory for this (following Patil et al, 1995). Finally, we propose to consider how we might extend the RSBLUQE theory for non-normal populations commonly used in environmental investigations.…”
Section: Best Linear Unbiased Quantile Estimation With Ranked Set Sammentioning
confidence: 95%
“…Table 1 represents the structure of RSS. For more details about RSS (Jozani and Johnson, 2011;Kowalczyk, 2004;Patil et al, 1995;Takahasi and Futatsuya, 1998).…”
Section: Ranked Set Sampling Proceduresmentioning
confidence: 99%